Penyelesaian Kasus Laka Lantas Yang Menimbulkan Korban Kematian Melalui Restoratif Justice (Studi Pada Satlantas Polrestabes Medan) - Bahajjad, Omar Abdul Rahman; Sitorus, Nanang Tomi (JUNCTO: Jurnal Ilmiah Hukum, 2025)
Traffic accidents resulting in fatalities have become a serious issue in Indonesia, including within the jurisdiction of the Medan Metropolitan Police (Polrestabes Medan). To pursue a more humane and efficient resolution, restorative justice has been implemented as an alternative to conventional litigation. This study aims to evaluate the effectiveness and challenges of implementing restorative justice in resolving fatal traffic accident cases. Using an empirical juridical approach, this research combines literature studies with in-depth interviews involving police officers and other related parties. The findings reveal that restorative justice significantly contributes to peaceful resolution through penal mediation, although its implementation still faces normative barriers, legal culture constraints, and public perception issues. The study concludes that despite the absence of explicit legal provisions, police discretion and strong local cultural support make restorative justice a relevant and effective approach in addressing traffic accident cases with fatal outcomes in society.